2021
DOI: 10.1093/gbe/evab078
|View full text |Cite
|
Sign up to set email alerts
|

The More, the Merrier? Multiple Myoglobin Genes in Fish Species, Especially in Gray Bichir (Polypterus senegalus) and Reedfish (Erpetoichthys calabaricus)

Abstract: The members of the globin superfamily are a classical model system to investigate gene evolution and their fates as well as the diversity of protein function. One of the best-known globins is myoglobin (Mb), which is mainly expressed in heart muscle and transports oxygen from the sarcolemma to the mitochondria. Most vertebrates harbor a single copy of the myoglobin gene, but some fish species have multiple myoglobin genes. Phylogenetic analyses indicate an independent emergence of multiple myoglobin genes, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…The ectopic occurrence of MB in tissue beyond skeletal/myocardial muscle was first reported in the liver and other organs of hypoxia-tolerant fish models [ 6 8 ]. More recently, we and others found that MB is expressed in several cancer cell lines and epithelial tumors [ 9 11 ] and in mouse brown adipose tissue [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ectopic occurrence of MB in tissue beyond skeletal/myocardial muscle was first reported in the liver and other organs of hypoxia-tolerant fish models [ 6 8 ]. More recently, we and others found that MB is expressed in several cancer cell lines and epithelial tumors [ 9 11 ] and in mouse brown adipose tissue [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ectopic occurrence of Mb isoforms in tissues different from skeletal/myocardial muscle was first reported in the liver and other organs of hypoxia-tolerant fish models [ 27 29 ]. More recently, Mb was found to be expressed in several cancer cell lines and epithelial tumors [ 7 , 30 , 31 ] and in mice brown adipose tissue [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…To assemble a dataset of TE content across major ray-finned fish lineages, we integrated the results of the repeat analysis of the P. bichir genome with other publicly available analyses of transposable elements in ray-finned fishes. For non-teleosts, this captured TE content from two additional polypteriform genomes for E. calabaricus (Helfenrath et al 2021) and P. senegalus (Fujito and Nonaka 2012), Acipenser ruthenus (Du et al 2020) as a representative of Chondrostei, as well as Lepisosteus oculatus (Braasch et al 2016), L. osseus (Mallik et al 2023), and Amia calva (Thompson et al 2021) as representative holosteans. These data were integrated with data from 98 teleost genomes previously analyzed for TE content (Reinar et al 2023), that capture the majority of major teleost lineages including Elopomorpha, Osteoglossomorpha, Otocephala, and a large number of acanthomorph and non-acanthomorph euteleosts.…”
Section: Comparative Analyses Of the Actinopterygian Mobilomementioning
confidence: 99%
“…Similarly, the sequencing of the Senegal bichir (Polypterus senegalus) leveraged the anatomy of polypterids to provide critical insights into how vertebrates achieved the transition from water to land (Bi et al 2021). In addition, the recently sequenced genome of a second polypterid, Erpetoichthys calabaricus [Reedfish; Assembly (ErpCal1.1; NCBI Annotation Release 100)], has been deployed alongside the P. senegalus genome to provide further insights into other aspects of early vertebrate diversification that include the evolution of keratins (Kimura and Nikaido 2021), olfactory receptors (Zhang et al 2021), and numerous other traits (Helfenrath et al 2021;Mikami et al 2022). However, based on BUSCO scores, the currently sequenced genome of P. senegalus, remains incomplete.…”
Section: Introductionmentioning
confidence: 99%